Exercised-based cardiac rehabilitation associates with lower all-cause mortality in patients with primary pulmonary hypertension - Kleinnibbelink, Geert; Buckley, Benjamin J. R.; Harrison, Stephanie L.; Williams, Nefyn; Fazio-Eynullayeva, Elnara; Underhill, Paula; van Dijk, Arie P. J.; Lip, Gregory Y. H.; Thijssen, Dick H. J. (Frontiers in Sports and Active Living, 2023)
Background Despite pharmacological therapies to improve outcomes of pulmonary hypertension (PH), poor long-term survival remains. Exercised-based cardiac rehabilitation (ExCR) may be an alternative strategy to improve prognosis. Therefore, using an electronic medical record (EMR) database, the objective of this study was to compare mortality between patients with primary PH with ExCR vs. propensity-matched PH patients without ExCR. Methods The retrospective analysis was conducted on February 15, 2023 using anonymized data within TriNetX, a global federated health research network. All patients were aged ≥18 years with primary PH recorded in EMRs with at least 1-year follow-up from ExCR. Using logistic regression models, patients with PH with an EMR of ExCR were 1:1 propensity score-matched with PH patients without ExCR for age, sex, race, and comorbidities, and cardiovascular care. Results In total, 109,736 patients with primary PH met the inclusion criteria for the control group and 784 patients with primary PH met the inclusion criteria for the ExCR cohort. Using the propensity score-matched cohorts, 1-year mortality from ExCR was proportionally lower with 13.6% (n = 101 of 744 patients) in the ExCR cohort compared to 23.3% (n = 174 of 747 patients) in the controls (OR 0.52, 95% CI 0.40–0.68). Conclusion The present study of 1,514 patients with primary PH suggests that ExCR is associated with 48% lower odds of 1-year mortality, when compared to propensity score-matched patients without ExCR.